The Effect of Environment Social Governance (ESG) and Financial Performance on Firm Value Moderated by Firm Size - Intan, Tamara; Paramita, Veronika Santi (Indonesian Scientific Publication, 2025)
In 2019, a report on GHG emissions in the energy industry sector revealed that the industry was responsible for the highest concentration of such gases and contributed to the decline in the company value of energy sector companies. Environmental Social Governance (ESG), Return on Asset (ROA), and Firm Size are contributing variables to the decline in the value of the firm. This study was conducted to assess whether the value of energy sector companies registered on the IDX in 2019-2023 is affected by ESG, ROA, and company size. A quantitative causality descriptive methodology was applied in this research. The data type uses panel and secondary data sources. Researchers set eighty-three companies in the energy industry registered on the Indonesia Stock Exchange as the population. Purposive sampling is the method employed, which sets the number of samples at 12 energy sector companies. The findings of this study partially reveal that ESG negatively affects firm value. Meanwhile, there is a positive effect between ROA and firm value. ESG and ROA simultaneously impacts firm value. The relationship between ESG and ROA cannot be moderated by firm size.